Developing Classroom Assessment Tool using Learning Management System-based Computerized Adaptive Test in Vocational High Schools - Hadi, Samsul; Haryanto, Haryanto; AM, Muh. Asriadi; Marlina, Marlina; Rahim, Abdul (Journal of Education Reseach and Evaluation, 2022)
Computers have taken on a large role in education, including testing and evaluation. Traditional tests that aren't comprehensive and don't distinguish between students' beginning talents lead to measurement findings that aren't representative of their true abilities. This study aims to develop and test assessment tool eligibility class that is used as an LMS-based adaptive. This type of research includes development research. The respondents of this study were experts who assessed the validation and students of SMK Electrical Power Installation Engineering Expertise Competencies. The data analysis technique used item response theory, classical test theory and descriptive statistics. Item analysis using the Rasch Model showed 10 items were not fit and the remaining 50 items were fit. Classical test theory analysis items with less validity there are 0 items, moderate there are 55 items, and high there are 5 items, with an Alpha reliability of 0.934. The attitude questionnaire developed consists of 8 items. There are 0 items with less validity, 6 items being moderate, and 2 items high, with an Alpha reliability of 0.731. The developed observation guide contains 16 observations. Items with less validity have 0 items, while there are 15 items, and 1 item high. The use of CAT-assisted learning management systems on research tools greatly facilitates teachers in conducting research accurately and practically.